Sexual dimorphism in upper gastrointestinal motility is dependent on duration of fast, time of day, age, and strain of mice. Issue 9 (3rd June 2019) - Soni, Krishnakant G.; Halder, Tripti; Conner, Margaret E.; Preidis, Geoffrey A.
Abstract: Background: An important limitation of gastrointestinal motility testing is high variability. Conditions that could contribute to variability, including the duration of pretest fasting and time of day, are rarely reported and have not been examined systematically. This study aimed to explore whether these conditions, as well as age, sex, and strain of mice, affect the results of a standard laboratory test of upper gastrointestinal motility. Methods: Male and female 8‐week‐old C57BL/6J mice received a gastric gavage of fluorescein isothiocyanate (FITC)‐conjugated dextran. FITC‐dextran distribution was measured 30 minutes later. Mean geometric centers (MGCs) were calculated to determine the effects of short versus prolonged fasting and morning versus afternoon testing. The influence of age was assessed in 2‐ to 10‐week‐old animals, and the influence of strain was determined in C57BL/6J, BALB/c, and CD‐1 mice. Key results: Motility was sexually dimorphic. MGC progressed 19% further in 8‐week‐old C57BL/6J males versus females when tested in the morning after a short fast. Similar patterns were observed in morning or afternoon testing after overnight fasting. In males, motility was unaffected by time of day; however, MGC progressed 31% further in females tested in the afternoon versus morning after a short fast. Sex differences also were present in CD‐1 but not BALB/c mice. Testing in neonates revealed strikingly low variability and no sex differences. Conclusions & inferences: Fasting duration, time of day, age, sex, and strain of mice all influence upper gastrointestinal motility testing. Sex differences are not present in neonatal pups, but develop soon after weaning. Abstract : High variability limits the utility of gastrointestinal motility testing; thus, we sought to determine how altering‐specific experimental conditions influence motility in mice. Gastrointestinal motility is faster in males versus females at 8 weeks of life when testing is performed in the morning following a short fast in C57BL/6J and CD‐1, but not BALB/c, mice. Adapting the test to neonates yields surprisingly low variability and no sex differences.